2020
DOI: 10.3390/geosciences10050189
|View full text |Cite
|
Sign up to set email alerts
|

Previous, Current, and Future Trends in Research into Earthquake Precursors in Geofluids

Abstract: Hazard reduction policies include seismic hazard maps based on probabilistic evaluations and the evaluation of geophysical parameters continuously recorded by instrumental networks. Over the past 25 centuries, a large amount of information about earthquake precursory phenomena has been recorded by scholars, scientific institutions, and civil defense agencies. In particular, hydrogeologic measurements and geochemical analyses have been performed in geofluids in search of possible and reliable earthquake precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 154 publications
0
24
0
Order By: Relevance
“…Once the most appropriate mechanism will be precisely assessed for the solar-earthquake interactions, is could likely represent a powerful element to help in earthquake forecast. Actually, a large number of methods devoted to earthquake forecast have been implemented: an extensive review can be found, for example, in Martinelli (2020), as far as geofluid precursors are concerned. Among the most promising methods, anyway, there is the "pattern recognition" approach (Rotwain and Novikova, 1999;Kossobokov et al, 2002;Peresan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Once the most appropriate mechanism will be precisely assessed for the solar-earthquake interactions, is could likely represent a powerful element to help in earthquake forecast. Actually, a large number of methods devoted to earthquake forecast have been implemented: an extensive review can be found, for example, in Martinelli (2020), as far as geofluid precursors are concerned. Among the most promising methods, anyway, there is the "pattern recognition" approach (Rotwain and Novikova, 1999;Kossobokov et al, 2002;Peresan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Rock permeability is in the range 10 −18 -10 −15 m at a depth of 10-20 km (Gleeson and Ingebritsen, 2017). These constraining parameters led Albarello (2015), Woith et al (2018) and Martinelli (2020) to propose that eventual precursory signals recorded in geofluids and as ground deformation may be considered as an indicator of the stress field evolution over time rather than signals generated by a hypothetical focal volume of a forthcoming seismic event.…”
Section: Data Selection Of Earthquake Precursorsmentioning
confidence: 99%
“…So, the circulation system of underground fluids could be affected by the same tectonic stress field at the strong interplate seismic zone in eastern Taiwan, the marginal seismic zone in western Taiwan and the intraplate seismic zone along the southeast coast of Fujian. According to the research results, the strain radius of a M6 earthquake can reach 380 km [72], so it could cause fluid mixing, deep fluid upwelling and water-rock reaction intensification when a M ≥ 6 earthquake within a few hundred kilometers nearby occurs, which would lead to changes in the ion concentration in the thermal springs [73]. This may be one of the reasons why the ion concentration in some thermal springs changed significantly before the Hualien M6.1 earthquake.…”
Section: Discussionmentioning
confidence: 97%